2022
DOI: 10.1016/j.clbc.2021.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Hospitalization Among Breast Cancer Patients With COVID-19: A Diverse Multi-Center Los Angeles Cohort Study

Abstract: Background The SARS-CoV-2 virus has infected and killed millions of people worldwide. Breast cancer is the most prevalent cancer in women and few studies have investigated the outcomes of patients with a history of breast cancer and COVID-19. We report the clinical outcomes of patients with invasive breast cancer who tested positive for SARS-CoV-2, including hospitalization and death, and evaluate demographic and cancer-related factors associated with these outcomes. Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“… COVID-19 imposes an increased risk of mortality in breast cancer patients. Kathuria-Prakash et al, USA 115 Observational study 1 Jan 2020–31 Dec 2020 132 (60 years) Hospitalization of breast cancer patients with COVID-19 Older age*, comorbidities**, lobular subtype*, and Hispanic/Latinx ethnicity* were significantly associated with hospitalization. Endocrine therapy might protect from worse conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… COVID-19 imposes an increased risk of mortality in breast cancer patients. Kathuria-Prakash et al, USA 115 Observational study 1 Jan 2020–31 Dec 2020 132 (60 years) Hospitalization of breast cancer patients with COVID-19 Older age*, comorbidities**, lobular subtype*, and Hispanic/Latinx ethnicity* were significantly associated with hospitalization. Endocrine therapy might protect from worse conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Older age, the presence of comorbidities, lobular subtype, and Hispanic/Latinx ethnicity were significantly associated with hospitalization due to COVID-19. 115 …”
Section: Resultsmentioning
confidence: 99%
“…A COVID-19 and Cancer Consortium (CCC19) registry-based study showed that Black cancer patients suffered from significantly more severe cases of COVID-19 than White patients, measured by a 5-level ordinal scale including hospitalization, mechanical ventilation, and all-cause mortality [6]. Kathuria-Prakash et al reported that Hispanic/Latinx ethnicity had a higher hospitalization rate among breast cancer patients with COVID-19 [7], and our results on GI cancer reflect a similar pattern. Also, based on the UC CORDS dataset, Kwon et al identified Hispanic ethnicity as a risk factor for hospitalization but no racial/ethnical disparities in mechanical ventilation and death within 30 days following COVID-19 among cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…A few epidemiological studies have investigated the racial disparities in clinical prognosis among cancer patients with COVID-19. A significantly increased risk of hospitalization and mortality for patients with cancer in general [3][4][5][6] or specific cancer (e.g., breast [7], gynecological [8], hematological [9], and prostate cancer [10]) was reported among racial minorities including African Americans (AA) or Blacks, American Indians and Alaska Natives (AI/AN), Asians and Pacific Islanders (API), and Hispanics.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the patients with antitumor treatment did not experience severe COVID-19, and no exacerbation of symptoms was observed even in patients who were still symptomatic at the time of antitumor therapy. Previous studies showed that advanced age and comorbidities were significantly associated with hospitalization ( 20 ). In our study, the average age of patients is less than 60 years old, so there were fewer comorbidities.…”
Section: Discussionmentioning
confidence: 99%